Pembinaan Sikap Disiplin dan Tawassuth Pada Santri Pondok Pesantren Salafiyah Darussalam Boyolali - Wulandari, Tri; Zaman, Badrus (LP2M IAIN kUDUS, 2022)
This study aims to describe the fostering of discipline and Tawassuth of students and to describe the impact of fostering discipline and Tawassuth of students at the Salafiyah Darussalam Boyolali Islamic Boarding School. This research uses qualitative research. This research uses data collection techniques through structured interviews with the presence of researchers in the field, observation, and documentation. Data analysis was used, namely: data reduction, data presentation, and drawing conclusions and verification. The results of the study show that: 1. Fostering discipline and Tawassuth students through giving advice, exemplary and scheduled activities such as congregational prayers, recitation, dziba activities, tahlil activities, simaan, rote memorization, roan, and activities with the community. 2. The impact of fostering disciplinary attitudes and Tawassuth students from disciplinary attitudes, namely: The impact of fostering disciplinary attitudes on students at the Salafiyah Darussalam Islamic Boarding School, namely: Compliance with regulations in Islamic boarding schools, disciplinary attitudes related to the completion of learning assignments, the obedience of students during class hours, as well as in fostering a disciplinary attitude there are sanctions for those who violate it. Then the impact of fostering the attitude of Tawassuth is: Establishing friendship between people so that divisions do not arise, students do not discriminate between groups or groups in interacting and communicating, accept opinions from other people who have different opinions and students can receive suggestions, input and constructive criticism from others.